Occurrence and risk assessment of per- and polyfluoroalkyl substances (PFASs) in water, sediment, soil, and moss: An environmental media study in Caohai, China - Luolin Bao; Chan Xu; Chan Zhang; Fenglian Zeng; Bangnian Xu; Chaoxuan Liao; Hongbo Yang (Emerging Contaminants)
Per- and polyfluoroalkyl compounds, also known as ''forever chemicals'', are ubiquitous in the environment and harm human health. Developing safer, eco-friendly alternatives is vital, but new compounds may cause new issues. Enhanced monitoring and risk assessment are essential. In this study, the detection of PFASs in environmental media, including lake surface water, bottom sediment, soil, and bryophytes, was accomplished by instrumentation in the Caohai region. Subsequently, their distribution characteristics and ecological risks were scientifically analyzed and evaluated. The results showed that new and traditional PFASs were widely found in Caohai, a non-industrial area, and showed obvious short-chain and new PFAS substitution effects. The total concentrations of PFASs (ΣPFASs) in surface water and sediment were measured at 39.55–67.64 ng/L and 2.36–11.55 ng/g dry weight (dw), respectively. The concentrations of ΣPFASs in soil and moss ranged from 0.39 to 1.31 ng/g dw and from 8.90 to 18.07 ng/g dw, respectively. Notably, PFBA and F-53B emerged as the most prevalent PFAS compounds in this region. The calculated risk quotients (RQs) for PFASs are less than 0.01, indicating no significant environmental risk. However, the long-term cumulative risk cannot be ignored, and the ecological protection of Caohai still needs to be paid attention to. The results of this study can help understand the pollution level of PFASs in the wetland water system in plateau areas and provide data references for environmental control such as PFASs pollution protection and ecological management in Caohai.